2012
DOI: 10.5915/43-3-8972
|View full text |Cite
|
Sign up to set email alerts
|

Ethical dilemmas in decision making at limits of neonatal viability

Abstract: The survival rate for extremely preterm infants has improved over the last two decades. Although the incidence of such births is about 2%, the impact of preterm birth on these infants, their families, health-care providers, and society is profound. The birth of an extremely low birth weight (ELBW) and early gestational age infant poses complex medical, social, and ethical challenges to the family and health-care professionals. Survivors have an increased risk of chronic medical problems and disability. It is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
7
0
3
Order By: Relevance
“…The third was a prolimitation class that consisted of instructors who presented zero probability of performing advanced resuscitation in infants born at 23-25 weeks of gestation and an intermediate probability of performing advanced resuscitation in infants born at 26 weeks of gestation. The three profiles of paediatricians identified in the current study showed different views about the application of advanced life support measures in the delivery room and reflect the existing doubts regarding the resuscitation of extremely premature infants born at the limit of viability (18)(19)(20)(21). One defined group of physicians in our study said that they would provide access to all available technology and would assume the risk of the possible outcomes, such as death with pain and suffering, survival with major or minor impairments and survival without impairments.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The third was a prolimitation class that consisted of instructors who presented zero probability of performing advanced resuscitation in infants born at 23-25 weeks of gestation and an intermediate probability of performing advanced resuscitation in infants born at 26 weeks of gestation. The three profiles of paediatricians identified in the current study showed different views about the application of advanced life support measures in the delivery room and reflect the existing doubts regarding the resuscitation of extremely premature infants born at the limit of viability (18)(19)(20)(21). One defined group of physicians in our study said that they would provide access to all available technology and would assume the risk of the possible outcomes, such as death with pain and suffering, survival with major or minor impairments and survival without impairments.…”
Section: Discussionmentioning
confidence: 77%
“…The three profiles of paediatricians identified in the current study showed different views about the application of advanced life support measures in the delivery room and reflect the existing doubts regarding the resuscitation of extremely premature infants born at the limit of viability . One defined group of physicians in our study said that they would provide access to all available technology and would assume the risk of the possible outcomes, such as death with pain and suffering, survival with major or minor impairments and survival without impairments.…”
Section: Discussionmentioning
confidence: 79%
“…As a basic principle, prenatal consultations should inform parents properly, comprehensively, compassionately, and in an understandable language. 3,16 Regarding parents' needs during prenatal consultations, Yee and Sauve found that, in a rank order, parents desire information on chances of survival, medical problems the child might have, the risk of mental or physical disabilities, medical treatment the child might need, and breastfeeding. 12 Information about the assumed medical condition of the unborn child, and the expectations for his/her likely short-and long-term prognosis should be provided on survival and follow-up statistics for the specific NICU as well as nationwide data.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the preferred way of prenatal counseling at the threshold of viability, most authors make a case for a nondirective approach enabling the parents to participate in a shared decision making which is medically appropriate and consistent with their own personal values and goals as well as the best interest of the child. 16,17,19 However, as to this approach, it is argued that it places an unfair burden on parents who later may regret their decision, whatever it was, and experience feelings of guilt.…”
Section: Discussionmentioning
confidence: 99%
“…Известно, что психологическое благополучие матери служит одним из условий успешного выхаживания недоношенных детей [6,7]. Первой ступенью вхождения в социальную среду ребенка с особенностями развития (у глубоконедоношенных детей это более позднее, чем у доношенных, формирование различных навыков и умений) является его адаптация в семье.…”
Section: оригинальные статьиunclassified